Metal and metal-free photocatalysts: mechanistic approach and application as photoinitiators of photopolymerization - Lalevée, Jacques; Telitel, Sofia; Xiao, Pu; Lepeltier, Marc; Dumur, Frédéric; Morlet-Savary, Fabrice; Gigmes, Didier; Fouassier, Jean-Pierre (Beilstein Journal of Organic Chemistry, 2014)
In the present paper, the photoredox catalysis is presented as a unique approach in the field of photoinitiators of polymerization. The principal photocatalysts already reported as well as the typical oxidation and reduction agents used in both reductive or oxidative cycles are gathered. The chemical mechanisms associated with various systems are also given. As compared to classical iridium-based photocatalysts which are mainly active upon blue light irradiation, a new photocatalyst Ir(piq)2(tmd) (also known as bis(1-phenylisoquinolinato-N,C2’)iridium(2,2,6,6-tetramethyl-3,5-heptanedionate) is also proposed as an example of green light photocatalyst (toward the long wavelength irradiation). The chemical mechanisms associated with Ir(piq)2(tmd) are investigated by ESR spin-trapping, laser flash photolysis, steady state photolysis, cyclic voltammetry and luminescence experiments.
Keywords: LEDs; photoinitiators; photopolymerization; photoredox catalysis